Life cycle assessment of bioethanol from wheat and sugar beet discussing environmental impacts of multiple concepts of co-product processing in the context of the European Renewable Energy Directive. Issue 2 (3rd March 2016) - Buchspies, Benedikt; Kaltschmitt, Martin
ABSTRACT: The environmental performance of biofuels is often assessed comparing multiple feedstocks while implications of different co-product processing options are neglected. This study presents a life cycle assessment of several co-product processing concepts of wheat- and sugar beet-based ethanol production in Germany. Inventory data are first-hand industry data presenting state-of-the-art plants. The methodology defined by the Renewable Energy Directive (RED) is applied. The cradle-to-gate investigation shows that the co-production of fodder results in lowest impacts allocated to ethanol: 37 g CO2 -eq. per MJ of ethanol from sugar beets. Total impacts are lower in case of beet-based ethanol in impact categories which are dominated by emissions from cultivation, such as eutrophication and acidification. Biogas co-production results in lowest total emissions but in higher emissions allocated to ethanol. A sensitivity analysis shows how certain assumptions, such as using a different energy carrier, grain drying, etc., influence these results. Results indicate that the environmental impacts of different co-product processing concepts differ. Consequently, special attention should be given to this aspect when the environmental impacts of biofuels are compared. It is furthermore advised to apply a method accounting for the utility and benefits of co-products when allocating emissions, as opposed to RED methodology.